HLA-DR(+) Immature Cells Exhibit Reduced Antigen-Presenting Cell Function But Respond to CD40 Stimulation* - Pinzon-Charry, Alberto (Neoplasia Press Inc., 2005)
Dendritic cells (DC) have been implicated in the defective function of the immune system during cancer progression. We have demonstrated that patients with cancer have fewer myeloid (CD11c(+)) and plasmacytoid (CD123(hi)) DC and a concurrent accumulation of CD11c(-)CD123(-) immature cells expressing HLA-DR (DR(+)IC). Notably, DR(+)IC from cancer patients have a reduced capacity to stimulate allogeneic T-cells. DR(+)IC are also present in healthy donors, albeit in smaller numbers. In this study, we assessed whether DR(+)IC could have an impact on the immune response by comparing their function with DC counterparts. For this purpose, DR(+)IC and DC were purified and tested in the presentation of antigens through major histocompatibility complex (MHC) II and MHC-I molecules. DR(+)IC were less efficient than DC at presenting antigens to T-cells. DR(+)IC induced a limited activation of T-cells, eliciting poor T-helper (Th) 1 and preferentially inducing Th2-biased responses. Importantly, despite DR(+)IC's poor responsiveness to inflammatory factors, in samples from healthy volunteers and breast cancer patients, CD40 ligation induced phenotypic maturation and interleukin 12 secretion, in turn generating more efficient T-cell responses. These data underscore the importance of inefficient antigen presentation as a mechanism for tumor evasion and suggest an approach to improve the efficacy of DC-based immunotherapy for cancer.